JAMU MADURA : EKSISTENSI, EKSPEKTASI DAN REALITAS PENGEMBANGANNYA DALAM PERSPEKTIF PRODUSEN DAN KONSUMEN - Selvia Nurlaila (MADURANCH: Jurnal Ilmu Peternakan, 2013)
Madura Island has a reputation as one of the herbs that have been tested by the National empirical use. Jamu Madura has tremendous potential as a non-food and agri products have a heritage and cultural identity that should always be preserved. The purpose of this study was to analyze the existence, expectation and reality Jamu Madura development from the perspective of producers and consumers. Type a descriptive study with qualitative methods. Location of study include Sumenep, Pamekasan and Sampang. The experiment was conducted in January to June 2013. Analysis of the data using interactive model. Existence of Jamu Madura is still running and is predicted to achieve an increase in line with the persistence of the production at the producer level and at the level of consumer purchases. Jamu Madura types can be classified into 3 types namely (a) the herbal treatment for women; (b) Herb married couples (couples) and (c) medicinal couples and illness (complete). Marketing Herbalist has spread on the island of Madura Madura, big cities such as Jakarta, Surabaya, Malang, Jawa also reaches beyond even to foreign countries. Expectations of producers and consumers Jamu Madura. Herbal medicine as a cultural heritage that should be preserved and developed. Jamu Madura effort is still to be developed with the production of herbal medicine, the benefits received by producers and sales are still running. Belief according to both producer and consumer perspectives on Jamu Jamu Madura Madura that can heal even though the process is slow but it is not detrimental to health. Jamu Madura proven efficacy perceived by consumers. Jamu Madura reality development consists of efforts include the development of raw materials, product diversification, development, marketing, packaging improvement, human resource development (HRD) research and development. Relevant stakeholders such as the Association of herbal medicine, community leaders, banking, cooperatives and producers need to be aware kompetitior